MENINGKATKAN KADAR NITROGEN PUPUK ORGANIK PELEPAH SAWIT UNTUK MENDAPATKAN RASIO C/N IDEAL - Sunarti, Sunarti; Hasibuan, Ikhsan (University of Prof. Dr. Hazairin, SH, 2020)
An intensive research about the application of Oil palm frond (OPF) organic fertilizer on paddy rice and soybean had been done for consecutive three years. The crops showed better growth and yield by years by OPF organic fertilizer compared to farmyard manure and chemical fertilizer. This finding was due to the adequate nutrient contents in OPF organic fertilizer which consist of more than 4% of N, P and K as required by national organic standard (SNI). However, the C/N ratio was rather high which more than 25%. This research aimed to evaluate new formulations of OPF organic fertilizer with the intention of finding ideal C/N ratio as required by SNI. In order to meet this objective, the study was conducted by mixing OPF chopped with various high N content organic materials. The best formulation was mixing of OPF chopped with oil palm leaves, farmyard manure and fish waste liquid fertilizer. The N content in this new formulation was 2.10% which was higher than previous OPF formulation 1.52%. Thus the C/N ratio became much lower in new formulation compared to previous one, 13.83% and 35.96% consecutively.